Efektivitas Pelaksanaan Diklat Calon Guru Penggerak Angkatan 4 Berdasarkan Model Evaluasi Kirkpatrick di Balai Besar Guru Penggerak (BBGP) - Nisa, Ikrima Thohorun; Sutarsih, Cicih; Sudarsyah, Asep (Jurnal Tata Kelola Pendidikan, 2023)
This study aims to determine the level of effectiveness of training in the 4th batch of teacher mobilizer program organized by the West Java Teacher Mobilizer Center (BBGP). Measurement of the effectiveness of education and training uses the Kirkpatrick evaluation model, with 4 levels, namely: level 1 (reaction), level 2 (learning), level 3 (behavior), and level 4 (result). The research method used in this study is a descriptive research method with a qualitative approach. Data collection techniques through interviews and documentation studies. Then checking the validity of the data is done by triangulation of techniques and sources. The results showed that the Implementation of Training for Prospective Teacher Movers Batch 4 Based on the Kirkpatrick Evaluation Model at the West Java Center for Teacher Movers (BBGP) at levels 1 and 2 was considered effective but at levels 3 and 4 it was not considered effective.